A metal porphyrin-based porous ionic polymer and its preparation method and application
By developing metalporphyrin-based porous ionic polymers, using their three-dimensional structure and mesoporous properties, combining the synergistic effects of metal centers and halogen ions, the existing catalyst efficiency and selectivity are solved, and efficient catalytic carbon dioxide cycloaddition reaction is achieved and production costs are reduced.
Patent Information
- Application Number
- CN202211355858.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-01
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-11-01
AI Technical Summary
The current metalporphyrin-based porous organic polymers have low efficiency and selectivity in catalyzing carbon dioxide cycloaddition reactions, and the catalyst is difficult to reuse and has high production costs.
A metalporphyrin-based porous ionic polymer was developed with the general formula of [M-R1-(R)4]n. By introducing R groups, it forms a three-dimensional structure, rich in mesoporous and high specific surface area, combining the synergistic effects of metal centers and halogen ions, improving catalytic efficiency and selectivity.
The efficient and selective catalyzed cycloaddition reaction between carbon dioxide and epoxide is achieved, and the yield of cyclic carbonate can reach 99.9%, and the catalyst is stable, easy to reuse, reducing production costs.
Smart Images

Figure CN115894871B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer compound catalysis, and more specifically, to a metal porphyrin-based porous ionic polymer and a preparation method and application thereof. Background Art
[0002] Excessive carbon dioxide emissions are the main cause of global warming. In order to alleviate the environmental crisis, it is urgent to develop a new catalytic system for the efficient conversion of carbon dioxide. Among the many technical routes for the resource utilization of carbon dioxide, the cycloaddition reaction of carbon dioxide with epoxides to form cyclic carbonates is currently one of the most promising and effective methods for fixing carbon dioxide, with the advantages of cheap raw materials, high atomic utilization rate, and few by-products.
[0003] Various catalytic systems have been developed to catalyze the cycloaddition reaction of epoxides with carbon dioxide. Porous organic polymers have attracted increasing attention in gas / liquid separation, gas storage, catalysis, etc. due to their high specific surface area and well-defined pore structure, stable framework, and the ability to introduce chemical functional groups into the skeleton to regulate porosity. However, the conditions for the catalytic synthesis of cyclic carbonates by such catalysts are currently rather complicated, and harsh conditions of high temperature and high pressure still exist. Homogeneous catalysts are difficult to separate and purify, and the catalysts are difficult to reuse, which increases production costs and consumes energy.
[0004] The prior art discloses an ionic liquid functionalized metal porphyrin-based porous organic polymer heterogeneous catalyst, a preparation method and an application thereof. The ionic liquid functionalized metal porphyrin-based porous organic polymer heterogeneous catalyst with azo bonds as bonding units can synergistically catalyze carbon dioxide and epoxide to synthesize cyclic carbonates under solvent-free and auxiliary agent-free conditions, but its catalytic conversion efficiency and selectivity for carbon dioxide still need to be improved. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of low efficiency and low selectivity of the existing metal porphyrin-based porous organic polymer catalyzed carbon dioxide cycloaddition reaction, and to provide a metal porphyrin-based porous ionic polymer with abundant mesopores, strong adsorption capacity for carbon dioxide, and the ability to catalyze the cycloaddition reaction of carbon dioxide and epoxide with high efficiency and selectivity.
[0006] Another object of the present invention is to provide a method for preparing the metalloporphyrin-based porous ionic polymer.
[0007] Another object of the present invention is to provide a metal porphyrin-based porous ion catalyst.
[0008] Another object of the present invention is to provide an application of a metal porphyrin-based porous ion catalyst in catalyzing carbon dioxide cycloaddition reaction.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A metal porphyrin-based porous ionic polymer, wherein the general formula of the metal porphyrin-based porous ionic polymer is: [M-R1-(R)4] n ;
[0011] The M is a metal atom;
[0012] The R1 is a porphyrin compound;
[0013] The R is selected from A, B, C,
[0014] Wherein, A is tetraphenylmethane and its derivatives without a halogen-containing ion liquid side chain; B is a tetraphenylmethane derivative with a halogen-containing ion liquid side chain; and C is a halogen-containing phosphonium salt.
[0015] It should be noted that:
[0016] In the metal porphyrin-based porous ion polymer of the present invention, the strong π-metal orbital coupling force between the metal and the porphyrin compound improves the stability of the catalytic site, and the metal porphyrin-based porous ion polymer is obtained by introducing the R group, and the polymer structure is rich in mesopores, which increases the specific surface area of the polymer, and is conducive to improving the catalytic efficiency and selectivity of the metal porphyrin-based porous ion polymer when used as a catalyst. And the metal porphyrin-based porous ion polymer also contains halogen ions, which can synergize with the electrophilic metal unit, so that the metal porphyrin-based porous ion polymer can efficiently and selectively perform catalytic reactions when used as a catalyst. Further, the R is B or C, and more specifically, R is B.
[0017] In addition, porphyrin as a nitrogen-rich organic compound can activate carbon dioxide molecules, and the metal center as a Lewis acid active site in the polymer can also activate carbon dioxide molecules. In the ring-opening reaction, the halogen ion as a nucleophilic attacking agent has a strong activation ability for epoxides and can accelerate the catalytic reaction.
[0018] The activation effect of various parts of the metal porphyrin-based porous ionic polymer on carbon dioxide and the rich nitrogen elements contained in the polymer are conducive to the selective adsorption of carbon dioxide, and the introduction of B and C or the modification of imidazole-based ionic liquid increases the interaction between the metal porphyrin-based porous ionic polymer and carbon dioxide, which can further selectively adsorb carbon dioxide. Therefore, the metal porphyrin-based porous ionic polymer of the present invention has a strong adsorption capacity for carbon dioxide and is also highly selective for carbon dioxide in the catalytic cycloaddition reaction of carbon dioxide and epoxide.
[0019] In the present invention, the metal porphyrin-based porous ionic polymer is characterized by being rich in mesopores and having a high specific surface area, and is capable of selectively adsorbing carbon dioxide, and carbon dioxide can be enriched around the metal center. In addition, the intramolecular synergistic effect between the metal unit and the B, C or imidazole-based ionic liquid further makes the metal porphyrin-based porous ionic polymer of the present invention have the characteristic of high selectivity.
[0020] In addition, since the coexistence of the metal center of the Lewis acid site and the halogen ion in the mesoporous polymer structure can achieve synergistic catalytic conversion of carbon dioxide into cyclic carbonates, the metal porphyrin-based porous ionic polymer of the present invention can also achieve a high yield of cyclic carbonates in the catalytic carbon dioxide cycloaddition reaction.
[0021] Specifically, when R is A, an imidazole-based ionic liquid is introduced into the metal porphyrin-based porous ionic polymer framework.
[0022] The chemical expression of the imidazolyl ionic liquid is: X is selected from I, Br or Cl.
[0023] When R is A, the introduction of the imidazole-based ionic liquid increases the density of polarizable active sites in the polymer, further improving the catalytic reaction efficiency of the metal porphyrin-based porous ionic polymer and enhancing the catalytic performance.
[0024] The B or C described in the technical solution of the present invention is also a type of ionic liquid.
[0025] Specifically, the R1 is selected from Wherein, M is Al or Co.
[0026] Specifically, the structural formula of B is Wherein, X is Br or Cl.
[0027] Specifically, the structural formula of C is Wherein, X is Br or Cl.
[0028] When the R group is selected from the above two structures, since the ionic liquid itself contains abundant halogen ions and can be cross-linked with the porphyrin skeleton containing the metal center through the Ullmann reaction, the obtained metal porphyrin-based porous ionic polymer has a higher ionic liquid content and a higher halogen ion content. When the metal porphyrin-based porous ionic polymer catalyzes the cycloaddition reaction of carbon dioxide, it has a stronger activation ability for the ring-opening reaction of epoxide and can more effectively promote the cycloaddition reaction of cyclic carbonate.
[0029] More specifically, the R is B: Wherein, X is Br or Cl.
[0030] The above-mentioned halogen-containing ion liquid contains nitrogen element in addition to halogen ions, which further increases the nitrogen content in the metal porphyrin-based porous ion polymer, can more effectively activate carbon dioxide molecules, and improve the selectivity for carbon dioxide.
[0031] Specifically, the mesopore area of the metal porphyrin-based porous ionic polymer is 30 to 350 cm 2 / g, more preferably 261 to 350 cm 2 / g.
[0032] Specifically, the specific surface area of the metal porphyrin-based porous ionic polymer is 130 to 900 cm 2 / g, more preferably 329 to 839 cm 2 / g.
[0033] The metal porphyrin-based porous ion polymer of the present invention is rich in mesoporous structure and has a large specific surface area, which increases the contact area with reactants during catalytic reactions and improves catalytic efficiency. In addition, the increase in mesoporous area and specific surface area is also beneficial to increasing the capacity for carbon dioxide, which is more conducive to the cycloaddition reaction of carbon dioxide.
[0034] Specifically, the metalloporphyrin-based porous ionic polymer has one of the following structures of group I or group II:
[0035] Group I:
[0036]
[0037]
[0038] Group II:
[0039] Preferably One of them.
[0040] The present invention also provides a method for preparing the above-mentioned metalloporphyrin-based porous ionic polymer:
[0041] When R is selected from A, the method comprises the following steps:
[0042] S1. Under an inert atmosphere, R1, R, a cross-linking agent and a catalyst are placed in an organic solvent or directly mixed uniformly for a first reflux reaction, and then cooled and separated and extracted to obtain a metal porphyrin-based polymer; wherein the first reflux temperature is 60 to 150 ° C, and the reaction time is 18 to 80 hours;
[0043] S2. placing the metal porphyrin-based polymer and polyformaldehyde in a mixture of glacial acetic acid, H3PO4 and concentrated HX for a second reflux reaction, and separating and extracting after cooling to obtain a metal porphyrin-based porous organic polymer; wherein X in the HX is one of Cl, Br, and I, the second reflux temperature is 60 to 100 ° C, and the reaction time is 48 to 96 hours;
[0044] S3. Under an inert atmosphere, placing the metal porphyrin-based porous organic polymer and N-methylimidazole in an organic solvent for a third reflux reaction, wherein the temperature of the third reflux reaction is 40 to 80° C., and the reaction time is 18 to 26 hours; after solid-liquid separation, purification is performed, and finally the metal porphyrin-based porous ionic polymer is extracted;
[0045] Wherein, the molar mass ratio of R1, R, catalyst and cross-linking agent in S1 is R1:R:catalyst:cross-linking agent=1:(1-2):(2-6):(2-6);
[0046] The cross-linking agent in S1 is one or two of dimethoxymethane, 1,4-dimethoxybenzene, chloroform, and dichloromethane;
[0047] The catalyst in S1 is one of bis(1,5-cyclooctadiene)nickel(0), ferric chloride, and aluminum chloride. When the catalyst is bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene need to be added as catalyst stabilizers;
[0048] The organic solvent in S1 is one of N,N-dimethylformamide, ethylene dichloride, and nitrobenzene;
[0049] The organic solvent in S3 is dichloromethane;
[0050] The specific operation of separation and extraction described in S1 can be referred to as follows:
[0051] After the reaction is completed, the mixture is cooled to room temperature, filtered, washed with acetone, extracted with Soxhlet, and dried to obtain a metalloporphyrin-based polymer;
[0052] The specific separation and extraction operations described in S2 can be referred to as follows:
[0053] After the reaction is completed, the mixture is cooled to room temperature, filtered, washed with N,N-dimethylformamide and dichloromethane, extracted with Soxhlet, and dried to obtain a metalloporphyrin-based porous organic polymer;
[0054] The solid-liquid separation, purification and extraction steps described in S3 can be specifically referred to as follows:
[0055] The suspension after the reaction was filtered under reduced pressure, washed with N,N-dimethylformamide and dichloromethane, extracted with methanol as a solvent, and dried at 60° C. for 12 hours to obtain a metalloporphyrin-based porous ionic polymer.
[0056] When R is selected from B or C, the method comprises the following steps:
[0057] S1. Under an inert atmosphere, R1, R, a catalyst and a catalyst stabilizer are placed in N,N-dimethylformamide to carry out an Ullmann reaction, wherein the reaction temperature is 60 to 120° C. and the reaction time is 24 to 48 h;
[0058] S2. After cooling to room temperature, HX is added to the reaction system for ion exchange, wherein the reaction temperature is 20 to 50° C., the reaction time is 6 to 10 hours, and the solid-liquid separation is followed by purification, and finally the metal porphyrin-based porous ionic polymer is extracted; wherein X in the HX is Br or Cl.
[0059] The molar mass ratio of R1, R, catalyst and catalyst stabilizer in S1 is R1:R:catalyst:catalyst stabilizer=1:1:(9-12):(9-12);
[0060] The solid-liquid separation, purification and extraction steps described in S2 can be specifically referred to as follows:
[0061] The suspension after the reaction was filtered under reduced pressure, washed with N,N-dimethylformamide and dichloromethane, and then Soxhlet extracted with acetone as a solvent, and then dried at 60° C. for 12 hours to obtain a metalloporphyrin-based porous ionic polymer.
[0062] The present invention specifically protects a metal porphyrin-based porous ion catalyst, wherein the catalyst contains the metal porphyrin-based porous ion polymer of the present invention.
[0063] The metal porphyrin-based porous ion polymer of the present invention has the characteristics of being rich in mesopores and having a large specific surface area. When performing a catalytic reaction, the contact area with the reactant is large, which is conducive to adsorbing the reactant, and the catalytic efficiency is high, and the selectivity for the reactant is also high. In addition, the metal porphyrin-based porous ion polymer catalyst is a highly stable multiphase catalyst, which does not require the addition of any solvent during the catalytic reaction, and has the characteristics of fast reaction rate, high yield of target product, and complete catalytic reaction in the multiphase catalytic reaction. The obtained product is easy to separate, and the catalyst can be effectively reused.
[0064] The present invention particularly protects the use of the metalloporphyrin-based porous ionic polymer in catalyzing the cycloaddition reaction of carbon dioxide and epoxide.
[0065] In the process of catalyzing the conversion of carbon dioxide and epoxide into cyclic carbonate, the metal porphyrin-based porous ion polymer of the present invention has the characteristics of rich mesopores and large specific surface area, which has a good promoting effect on the capture and utilization of carbon dioxide. The metal porphyrin-based porous ion polymer contains a metal center and a halogen ion as a nucleophilic attack reagent for the ring-opening reaction, and is rich in nitrogen elements. The metal center can activate carbon dioxide as an active site, and the nitrogen element can further adsorb and activate carbon dioxide. In the ring-opening reaction, the halogen ion has the ability to activate the epoxide. The triple activation is achieved by the metal center, the nitrogen element, and the halogen ion, which effectively promotes the cycloaddition reaction of carbon dioxide and epoxide, and improves the selectivity for carbon dioxide and the yield of cyclic carbonate.
[0066] The specific application method can refer to the following steps:
[0067] (1) adding a metal porphyrin-based porous ion catalyst and an epoxide into a reaction kettle, introducing carbon dioxide, and mixing and reacting at 25 to 100° C.;
[0068] (2) After the reaction, the mixture is cooled to room temperature and the filtrate obtained by separation is the cyclic carbonate solution.
[0069] Wherein, the amount of the metal porphyrin-based porous ion catalyst in step (1) is 0.05 to 2.5 mol%, preferably 0.15 to 0.25 mol%, more preferably 0.2 mmol / L of the epoxide; the pressure of the carbon dioxide is 0.1 to 3.0 MPa; the epoxide is wherein R2 is one of hydrogen, halogen, alkyl, unsaturated ether bond, and phenoxy, and R3 is one of hydrogen, halogen, alkyl, and alkoxy; preferably Wherein R2 is one of hydrogen, halogen, alkyl, unsaturated ether bond, and phenoxy group; R3 is one of hydrogen, halogen, alkyl, and alkoxy group; more preferably, it is one of epichlorohydrin, propylene oxide, 1,2-butylene oxide, and epibromohydrin; and more preferably, it is epichlorohydrin.
[0070] Compared with the prior art, the present invention has the following beneficial effects:
[0071] In the metal porphyrin-based porous ion polymer of the present invention, the strong π-metal orbital coupling force between the metal and the porphyrin compound makes the catalyst highly stable. The introduction of the R group makes the metal porphyrin-based porous ion polymer have a three-dimensional structure, rich in mesopores and large specific surface area, which is conducive to promoting the capture of carbon dioxide and improving the catalytic efficiency. In addition, the metal center, nitrogen element and halogen ion in the metal porphyrin-based porous ion polymer can further adsorb and activate carbon dioxide during the catalytic reaction process, thereby achieving efficient and highly selective catalysis of the cycloaddition reaction of carbon dioxide and epoxide, and the yield of cyclic carbonate can reach 99.9% after the reaction for 10 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 is an infrared spectrum of the metalloporphyrin-based porous ionic polymer of Example 1;
[0073] Figure 2 is the solid state NMR image of the metalloporphyrin-based porous ionic polymer of Example 6;
[0074] Figure 3 Specific surface area diagram of the metal porphyrin-based porous ionic polymer of Example 2 and Example 6;
[0075] Figure 4 This is a pore size test diagram of the metalloporphyrin-based porous ionomer of Example 2;
[0076] Figure 5 is an X-ray photoelectron diffraction energy spectrum narrow spectrum scanning spectrum of the metalloporphyrin-based porous ionic polymer of Example 6;
[0077] Figure 6 is a gas chromatogram of a cyclic carbonate solution obtained by a carbon dioxide cycloaddition reaction catalyzed by the metalloporphyrin-based porous ionic polymer of Example 4;
[0078] Figure 7 This is a gas chromatogram of the cyclic carbonate solution obtained by catalyzing the reaction of carbon dioxide and styrene oxide by the metalloporphyrin-based porous ionic polymer of Example 6. DETAILED DESCRIPTION
[0079] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0080] The mesopore area and specific surface area of the metal porphyrin-based porous ionic polymer are calculated as follows:
[0081] Mesopore area calculation: Mesopore area = total specific surface area - micropore area
[0082] Specific surface area calculation:
[0083] Among them, P is the partial pressure of the adsorbate; P0 is the saturated vapor pressure of the adsorbent; V is the actual adsorption amount of the sample; Vm is the monolayer saturated adsorption amount; C is a constant related to the sample adsorption capacity.
[0084] Example 1
[0085] A metalloporphyrin-based porous ionic polymer, wherein R1 is selected from M is a Co atom, and R is selected from (a tetraphenylmethane derivative without a halogen ion liquid side chain), the structure of the metal porphyrin-based porous ionic polymer is as follows, denoted as PL1:
[0086] Wherein, X is Br.
[0087] The above-mentioned metal porphyrin-based porous ionic polymer can be prepared by the following method:
[0088] S1. In an inert atmosphere, Bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene are placed in N,N-dimethylformamide for a first reflux reaction, cooled to room temperature and filtered, then washed with acetone, extracted with Soxhlet and dried to obtain a metalloporphyrin-based polymer;
[0089] Wherein, the first reflux temperature is 80°C, the reaction time is 28h, The molar mass ratio of bis(1,5-cyclooctadiene)nickel(0) is 1:1:10;
[0090] S2. placing the metal porphyrin-based polymer and polyformaldehyde in a mixed solution of glacial acetic acid, H3PO4 and concentrated HBr for a second reflux reaction, cooling to room temperature and filtering, then washing with N,N-dimethylformamide and dichloromethane, and drying after Soxhlet extraction to obtain a metal porphyrin-based porous organic polymer; wherein the second reflux temperature is 100° C. and the reaction time is 68 h;
[0091] S3. Under an inert atmosphere, the metal porphyrin-based porous organic polymer and N-methylimidazole are placed in dichloromethane for a third reflux reaction, wherein the temperature of the third reflux reaction is 60°C and the reaction time is 24 hours; the obtained suspension is filtered under reduced pressure, washed with N,N-dimethylformamide and dichloromethane, and then Soxhlet extraction is performed with methanol as solvent for 24 hours, and then dried in a vacuum drying oven at 60°C for 12 hours to finally obtain a metal porphyrin-based porous ionic polymer.
[0092] The calculated mesopore area of PL1 is 350 cm2 / g, specific surface area is 719cm 2 / g.
[0093] The infrared spectrum of PL1 was analyzed and the peak of PL1 at 1157 cm -1 and 1489cm -1 There are two absorption peaks, among which 1157cm -1 is the peak of CN bond in ionic liquid, 1489cm -1 The peaks are those of the CC bonds on the porphyrin ring or the tetraphenylmethane unit, indicating that the metal porphyrin-based porous ionic polymers with the corresponding structures have been successfully obtained.
[0094] Example 2
[0095] A metalloporphyrin-based porous ionic polymer, wherein R1 is selected from M is an Al atom, and R is selected from (tetraphenylmethane without a halogen ion liquid side chain), the metal porphyrin-based porous ionic polymer structure is as follows, denoted as PL2:
[0096] Wherein, X is Br.
[0097] The preparation method is the same as that of Example 1, except that (M is Co) is replaced by (M is Al), replace Replace with The bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene were replaced by ferric chloride and dimethoxymethane, the N,N-dimethylformamide in S1 was replaced by dichloroethane, the first reflux reaction temperature in S1 was 70°C, the reaction time was 22h, and the The molar mass ratio of ferric chloride and dimethoxymethane is 1:1:5:5.
[0098] The calculated mesopore area of PL2 is 265 cm 2 / g, with a specific surface area of 329cm 2 / g.
[0099] The infrared spectrum of PL2 was analyzed and the -1 and 1501cm -1 There are two absorption peaks, among which 1154cm -1 is the peak of CN bond in ionic liquid, 1501cm -1 The peaks are those of the CC bonds on the porphyrin ring or the tetraphenylmethane unit, indicating that the metal porphyrin-based porous ionic polymers with the corresponding structures have been successfully obtained.
[0100] Example 3
[0101] A metalloporphyrin-based porous ionic polymer, wherein R1 is selected from M is an Al atom, and R is selected from (tetraphenylmethane without a halogen ion liquid side chain), the metal porphyrin-based porous ionic polymer structure is as follows, denoted as PL3:
[0102] Wherein, X is Br.
[0103] The preparation method is the same as that of Example 1, except that (M is Co) is replaced by (M is Co), replace Replace with The bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene are replaced by ferric chloride and 1,4-dimethoxybenzene, the N,N-dimethylformamide in S1 is replaced by nitrobenzene, the first reflux reaction temperature in S1 is 100°C, the reaction time is 24h, and the The molar mass ratio of ferric chloride and 1,4-dimethoxybenzene is 1:1:2:5.
[0104] The calculated mesopore area of PL3 is 59 cm 2 / g, specific surface area is 142cm 2 / g.
[0105] The infrared spectrum of PL3 was analyzed and the -1 and 1539cm -1 There are two absorption peaks, among which 1150cm -1 is the peak of CN bond in ionic liquid, 1539cm -1 The peaks are those of the CC bonds on the porphyrin ring or the tetraphenylmethane unit, indicating that the metal porphyrin-based porous ionic polymers with the corresponding structures have been successfully obtained.
[0106] Example 4
[0107] A metalloporphyrin-based porous ionic polymer, wherein R1 is selected from M is an Al atom, and R is selected from (tetraphenylmethane without a halogen ion liquid side chain), the metal porphyrin-based porous ionic polymer structure is as follows, denoted as PL4:
[0108] Wherein, X is Br.
[0109] The preparation method is the same as that of Example 1, except that (M is Co) is replaced by (M is Al), replace Replace with The bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene are replaced by aluminum chloride and chloroform. N,N-dimethylformamide is not required in S1. The first reflux reaction temperature in S1 is 90° C. and the reaction time is 24 h. The molar mass ratio of aluminum chloride to chloroform is 1:1:6:2.
[0110] The calculated mesopore area of PL4 is 69 cm 2 / g, with a specific surface area of 222cm 2 / g.
[0111] The infrared spectrum of PL4 was analyzed and the -1 and 1581cm -1 There are two absorption peaks, among which 1162cm -1 is the peak of CN bond in ionic liquid, 1581cm -1 The peaks are those of the CC bonds on the porphyrin ring or the tetraphenylmethane unit, indicating that the metal porphyrin-based porous ionic polymers with the corresponding structures have been successfully obtained.
[0112] Example 5
[0113] A metalloporphyrin-based porous ionic polymer, wherein R1 is selected from M is an Al atom, and R is selected from (tetraphenylmethane without a halogen ion liquid side chain), the metal porphyrin-based porous ionic polymer structure is as follows, denoted as PL5:
[0114] Wherein, X is Br.
[0115] The preparation method is the same as that of Example 1, except that (M is Co) is replaced by (M is Al), replace Replace with The bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene are replaced by aluminum chloride and dichloromethane. N,N-dimethylformamide is not required in S1. The first reflux reaction in S1 is replaced by reacting at 60°C and 100°C for 28h respectively. The molar mass ratio of aluminum chloride to dichloromethane is 1:1:6:2.
[0116] The calculated mesopore area of PL5 is 61 cm2 / g, specific surface area is 583cm 2 / g.
[0117] The infrared spectrum of PL5 was analyzed and the peak of PL5 at 1147 cm -1 and 1555cm -1 There are two absorption peaks, among which 1147cm -1 is the peak of CN bond in ionic liquid, 1555cm -1 The peaks are those of the CC bonds on the porphyrin ring or the tetraphenylmethane unit, indicating that the metal porphyrin-based porous ionic polymers with the corresponding structures have been successfully obtained.
[0118] Example 6
[0119] A metalloporphyrin-based porous ionic polymer, wherein R1 is selected from M is a Co atom, and R is selected from (a tetraphenylmethane derivative having a halogen ion liquid side chain), wherein X is Cl, and the structure of the metal porphyrin-based porous ionic polymer is as follows, denoted as PL6:
[0120]
[0121] The above-mentioned metal porphyrin-based porous ionic polymer can be prepared by the following method:
[0122] S1. In an inert atmosphere, Bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene are placed in N,N-dimethylformamide to carry out Ullmann reaction, wherein the reaction temperature is 80° C., the reaction time is 28 h, and the The molar mass ratio of bis(1,5-cyclooctadiene)nickel(0) and 2,2'-bipyridine and 1,5-cyclooctadiene is 1:1:10:10, wherein the molar mass ratio of 2,2'-bipyridine to 1,5-cyclooctadiene is 1:1;
[0123] S2. After cooling to room temperature, HCl was added to the reaction system for ion exchange, wherein the reaction temperature was 40°C and the reaction time was 6 hours. After the reaction was completed, the obtained suspension was filtered under reduced pressure, washed with N,N-dimethylformamide and dichloromethane, and then Soxhlet extraction was performed with acetone as solvent for 24 hours, and then dried in a vacuum drying oven at 60°C for 12 hours to finally obtain a metal porphyrin-based porous ionic polymer.
[0124] The calculated mesopore area of PL6 is 261 cm 2 / g, with a specific surface area of 839 cm 2 / g.
[0125] The infrared spectrum of PL6 was analyzed and the -1 and 1439cm -1 There are two absorption peaks, among which 1140cm -1 The peak of CN bond in ionic liquid is 1439cm -1 The peaks are those of the CC bonds on the porphyrin ring or the tetraphenylmethane unit, indicating that the metal porphyrin-based porous ionic polymers with the corresponding structures have been successfully obtained.
[0126] Example 7
[0127] A metalloporphyrin-based porous ionic polymer, wherein R1 is selected from M is an Al atom, and R is selected from (containing halogen phosphonate), wherein X is Cl, and the structure of the metal porphyrin-based porous ionic polymer is as follows, denoted as PL7:
[0128]
[0129] The preparation method is the same as that of Example 6, except that (M is Co) is replaced by (M is Al), replace Replace with
[0130] The calculated mesopore area of PL7 is 53 cm 2 / g, with a specific surface area of 318cm 2 / g.
[0131] Infrared spectrum analysis of PL7 revealed that PL2 was -1 and 1649cm -1 There are two absorption peaks, 1250cm -1 The absorption peak at 1649 cm comes from the halogen-containing phosphonium salt unit. -1 It is the peak of CC bond on the porphyrin ring, indicating that the metal porphyrin-based porous ionic polymer with the corresponding structure is successfully obtained.
[0132] Results
[0133] 1. Cycloaddition reaction of carbon dioxide and epichlorohydrin:
[0134] (1) 0.2 mmol% (relative to the amount of epichlorohydrin) of each of the metalloporphyrin-based porous ionic polymers of Examples 1 to 7 were independently added to a 10 mL stainless steel autoclave with 3.0 mmol of epichlorohydrin;
[0135] Among them, Examples 1 to 5 correspond to the introduction of 1 MPa of carbon dioxide gas; Examples 6 to 7 correspond to the introduction of 0.5 MPa of carbon dioxide gas;
[0136] Examples 1 to 2 correspond to stirring the reaction at 80°C for 10 hours; Examples 3 to 4 correspond to stirring the reaction at 80°C for 12 hours; Example 5 corresponds to stirring the reaction at 80°C for 12 hours; Examples 6 to 7 correspond to stirring the reaction at 60°C for 10 hours.
[0137] (2) After the reaction, the mixture is cooled to room temperature, and the metal porphyrin-based porous ionic polymer is separated by filtration to obtain a cyclic carbonate solution.
[0138] The above test results are shown in Table 1.
[0139] 2. Cycloaddition reaction of carbon dioxide with propylene oxide, 1,2-butylene oxide, epibromopropane, allyl glycidyl ether, styrene oxide, and cyclohexane oxide:
[0140] (1) 0.2 mmol% of the metalloporphyrin-based porous ionomer of Example 6 was added to a 10 mL stainless steel autoclave with 3.0 mmol of propylene oxide, 1,2-butylene oxide, epibromopropane, allyl glycidyl ether, styrene oxide, and cyclohexane oxide, and 0.5 MPa of carbon dioxide gas was introduced;
[0141] Among them, the reaction was stirred with propylene oxide at 40°C for 16 hours; the reaction was stirred with 1,2-butylene oxide at 60°C for 12 hours; the reaction was stirred with epibromopropane at 40°C for 16 hours; the reaction was stirred with allyl glycidyl ether at 80°C for 20 hours; and the reaction was stirred with styrene oxide at 100°C for 48 hours.
[0142] (2) After the reaction, the mixture is cooled to room temperature, and the metal porphyrin-based porous ionic polymer is separated by filtration to obtain a cyclic carbonate solution.
[0143] The above test results are shown in Table 2.
[0144] Calculation of cyclic carbonate yield: Cyclic carbonate yield = actual cyclic carbonate production / theoretical cyclic carbonate production × 100%
[0145] Table 1. Yields of cyclic carbonates from the catalytic carbon dioxide cycloaddition reaction of Examples 1 to 7 and Comparative Examples 1 to 2
[0146] Cyclic carbonate yield (%) Example 1 98 Example 2 99.9 Example 3 99 Example 4 95 Example 5 98 Example 6 98 Example 7 95
[0147] As can be seen from Table 1, the metalloporphyrin-based porous ionomer of the present invention has high catalytic efficiency for the carbon dioxide cycloaddition reaction, and a cyclic carbonate yield of more than 95% can be obtained within a reaction time of 12 h. In addition, the cyclic carbonate yield of Examples 1 to 2 reaches more than 98% after reacting at 80° C. for 10 h, and the cyclic carbonate yield of Example 6 reaches 98% after reacting at 60° C. for 10 h. The catalytic efficiency is higher than that of other examples.
[0148] Table 2. Example 6 Catalytic Cycloaddition Reaction of Carbon Dioxide and Epoxide Cyclic Carbonate Yield
[0149] Epoxide Type Cyclic carbonate yield (%) Epichlorohydrin 98 Propylene oxide 99 1,2-Butane oxide 95 Epibromopropane 99 Allyl glycidyl ether 96 Styrene oxide 97
[0150] It can be seen from Table 2 that the metalloporphyrin-based porous ionic polymer of the present invention has good catalytic effect on the carbon dioxide cycloaddition reaction of different epoxides, and the yield of cyclic carbonate is above 95%.
[0151] Figure 1 The infrared spectrum of the metalloporphyrin-based porous ionic polymer of Example 1 is shown in the figure. As can be seen from the figure, the infrared spectrum at 1487 cm -1 and 1157cm -1 There are two peaks at 1487cm -1 The peak of the CC bond on the porphyrin ring or the tetraphenylmethane unit is 1157 cm -1 is the peak of the CN bond on the imidazole group, indicating that the metal porphyrin-based porous ionic polymer described in Example 1 of the present invention contains an imidazole ring.
[0152] Figure 2 The solid-state NMR image of the metal porphyrin-based porous ionic polymer of Example 6 is shown in the figure. As shown in the figure, the solid-state NMR shows that resonance peaks can be observed at 120, 127, 132, 140 and 147 ppm, which correspond to the carbon atoms on the porphyrin macrocycle and the aromatic ring, respectively; the peaks at 36 ppm and 52 ppm correspond to the methyl (-CH 3) and methylene (-CH2-) groups, which proves the presence of imidazole-based ionic liquids in the metal porphyrin-based porous ionic polymers described in Example 6 of the present invention; in addition, the peak at about 65 ppm corresponds to the sp3-C of the tetraphenylmethane group, which can prove that the metal porphyrin-based porous ionic polymers described in Example 6 of the present invention have the structure shown in Example 6.
[0153] Figure 3The specific surface area diagram of the metal porphyrin-based porous ionic polymer of Example 2 and Example 6 is shown in the figure. As the pressure increases, the adsorption amount gradually increases, and a hysteresis loop appears. This type of isothermal adsorption line belongs to a typical type I curve. It can be clearly seen that the specific surface area of the metal porphyrin-based porous ionic polymer obtained in Example 1 is 756 cm 2 ·g -1 The specific surface area of the metal porphyrin-based porous ionic polymer obtained in Example 6 is 839 cm 2 ·g -1 , which confirms that the metal porphyrin-based porous ionic polymer described in the present invention has a large specific surface area.
[0154] The metalloporphyrin-based porous ionic polymer in Example 2 was subjected to pore size detection to verify the formation of mesopores in the product. The results are as follows: Figure 4 As shown in the pore size test diagram, the pore size of the substance is mainly distributed in the micropore (below 2nm) area, but there is also a large distribution in the mesopore (2-50nm) area, indicating that the substance has both micropores and mesopores.
[0155] The metal porphyrin-based porous ionic polymer of Example 6 was subjected to X-ray photoelectron diffraction detection to verify the elemental composition of the product. The results are as follows: Figure 5 As shown, the X-ray photoelectron diffraction energy spectrum narrow spectrum scanning spectrum shows that it contains rich C, N, Al and a certain amount of Br elements, and the binding energy corresponding to the orbital energy level and its valence state are consistent with each other, proving that the metal porphyrin-based porous ionic polymer in Example 6 is rich in nitrogen elements, has active metal centers and halogen ions.
[0156] Figure 6 and Figure 7 It is a gas chromatogram of a cyclic carbonate solution. It can be seen from the spectrum that there are no other impurity peaks except the solvent, substrate and product, indicating that the metal porphyrin-based porous ionic polymer of the present invention has good selectivity for carbon dioxide. In addition, providing the corresponding gas chromatogram can further prove the yield of the corresponding cyclic carbonate.
[0157] It should be noted that although the remaining embodiments provide relevant descriptions of the results of their characterization spectra, their relevant properties are equivalent.
[0158] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A metalloporphyrin-based porous ionic polymer, characterized in that: The metal porphyrin-based porous ionic polymer has one of the following structures of group I or group II:
2. The metalloporphyrin-based porous ionic polymer according to claim 1, characterized in that: The mesopore area of the metal porphyrin-based porous ionic polymer is 30 to 350 cm 2 / g.
3. The metalloporphyrin-based porous ionic polymer according to claim 1, characterized in that: The specific surface area of the metal porphyrin-based porous ionic polymer is 130 to 900 cm 2 / g.
4. The method for preparing the metalloporphyrin-based porous ionic polymer according to any one of claims 1 to 3, characterized in that: The steps include: S1. Under an inert atmosphere, R1, R, a cross-linking agent and a catalyst are placed in an organic solvent or directly mixed uniformly for a first reflux reaction, and then cooled and separated and extracted to obtain a metal porphyrin-based polymer; wherein the first reflux temperature is 60 to 150 ° C, and the reaction time is 18 to 80 hours; S2. placing the metal porphyrin-based polymer and paraformaldehyde in a mixture of glacial acetic acid, H3PO4 and concentrated HX for a second reflux reaction, and separating and extracting after cooling to obtain a metal porphyrin-based porous organic polymer; wherein X in the HX is Cl or Br, the second reflux temperature is 60 to 100 ° C, and the reaction time is 48 to 96 hours; S3. Under an inert atmosphere, placing the metal porphyrin-based porous organic polymer and N-methylimidazole in an organic solvent for a third reflux reaction, wherein the temperature of the third reflux reaction is 40 to 80° C., and the reaction time is 18 to 26 hours; after solid-liquid separation, purification is performed, and finally the metal porphyrin-based porous ionic polymer is extracted; R1 is Wherein, M is Al or Co; R is tetraphenylmethane and its derivatives without a side chain containing a halogen ion liquid; Or include the following steps: S1. Under an inert atmosphere, R1, R, a catalyst and a catalyst stabilizer are placed in N,N-dimethylformamide to carry out an Ullmann reaction, wherein the reaction temperature is 60 to 120° C. and the reaction time is 24 to 48 h; S2. After cooling to room temperature, HX is added to the reaction system for ion exchange, wherein the reaction temperature is 20 to 50° C., the reaction time is 6 to 10 h, solid-liquid separation is performed, and purification is performed, and finally a metal porphyrin-based porous ionic polymer is extracted; wherein X in HX is Br or Cl; R1 is Wherein, M is Al or Co; R is Wherein, X is Br or Cl.
5. A metal porphyrin-based porous ion catalyst, characterized in that: The catalyst contains the metalloporphyrin-based porous ionomer according to any one of claims 1 to 3.
6. Use of the metalloporphyrin-based porous ion catalyst according to claim 5 in catalyzing the cycloaddition reaction of carbon dioxide and epoxide.
Citation Information
Patent Citations
Preparation of porous organic material and application in performing catalytic conversion on carbon dioxide
CN104667974A
Functional organic porous polymer as well as preparation method and application thereof
CN112724373A
Cited By
Ionic liquid functionalized metalloporphyrin porous copolymer as well as preparation method and application thereof
CN121975060A